A guide for arterial line insertion for the South African primary care practitioner - Indiran Govender; Henry I. Okonta; Olukayode Adeleke; Sunday Okeke (South African Family Practice)
This article provides information on the reasons for inserting an arterial line, how to insert this line, the equipment required to insert an arterial line, and the possible complications that may arise from this procedure. It is hoped this information will guide primary care practitioners working in the South African environment and increase their confidence for inserting arterial lines.